Being an accountant, cook, entertainer and teacher—all at the same time: Changes in employees' work and work‐related well‐being during the coronavirus (COVID‐19) pandemic. (7th April 2021) - Syrek, Christine; Kühnel, Jana; Vahle‐Hinz, Tim; de Bloom, Jessica
Abstract : In March 2020, the world was hit by the coronavirus disease (COVID‐19) pandemic which led to all‐embracing measures to contain its spread. Most employees were forced to work from home and take care of their children because schools and daycares were closed. We present data from a research project in a large multinational organisation in the Netherlands with monthly quantitative measurements from January to May 2020 ( N = 253–516), enriched with qualitative data from participants' comments before and after telework had started. Growth curve modelling showed major changes in employees' work‐related well‐being reflected in decreasing work engagement and increasing job satisfaction. For work‐non‐work balance, workload and autonomy, cubic trends over time were found, reflecting initial declines during crisis onset (March/April) and recovery in May. Participants' additional remarks exemplify that employees struggled with fulfilling different roles simultaneously, developing new routines and managing boundaries between life domains. Moderation analyses demonstrated that demographic variables shaped time trends. The diverging trends in well‐being indicators raise intriguing questions and show that close monitoring and fine‐grained analyses are needed to arrive at a better understanding of the impact of the crisis across time and among different groups of employees.